A cross-cultural study on the Köhler Motivation Gain Effect in team performance - Seok, DongHeon (Korean Journal of Industrial and Organizational Psychology, 2013)
The present study examined a factor that could contribute to cross-cultural differences in team performance (viz., age composition between team members) within one group motivation-gain paradigm (viz. the Köhler motivation gain, where a low-ability team member works harder in a team where they are the “weak link” than if s/he were working alone; Hertel, Kerr, & Messé, 2000a). In Exp. 1, I proposed that cultural difference between East Asians and Westerners(e.g., collectivism vs. individualism, interdependent vs. independent self-construal) could moderate the Köhler motivation gain effect, but the results showed that the culture did not moderate the Köhler effect. In Exp. 2, I found that age composition between group members (i.e., working with younger partner vs. older partner) might have different meaning in Korean culture compared to American culture. Finally, in Exp. 3., I conducted an experiment which extended the results of the Exp. 2 in two ways: 1) the Exp. 3 collected actual performance data rather than respondents’ intention to perform, as in the prior study, and 2) the Exp. 3 competitively tested alternative explanations for an age-of-partner effect in Korea. Both the performance results and subjective ratings of the present study suggested that the age effect in Korea could be explained in terms of participant’s felt responsibility in the task performance situation (i.e., Koreans felt more responsibility for the outcome of their group when they worked with a younger partner than an older partner). These results were discussed in terms of the social psychological implications of the deeply rooted Confucianism in Korean society (Koh, 1996). Limitations of the study and implications of the results for understanding existing cross-cultural theories were also discussed.